2020
DOI: 10.1371/journal.pone.0231517
|View full text |Cite
|
Sign up to set email alerts
|

On-line anxiety level detection from biosignals: Machine learning based on a randomized controlled trial with spider-fearful individuals

Abstract: We present performance results concerning the validation for anxiety level detection based on trained mathematical models using supervised machine learning techniques. The model training is based on biosignals acquired in a randomized controlled trial. Wearable sensors were used to collect electrocardiogram, electrodermal activity, and respiration from spiderfearful individuals. We designed and applied ten approaches for data labeling considering individual biosignals as well as subjective ratings. Performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 44 publications
0
58
1
Order By: Relevance
“…While the users watched the films, skin conductance was measured and recorded using electrodes on the index and middle finger of the left hand of the participant. The study reported that skin conductance response was not related to changes in anxiety levels, which is contradictory to the findings of other studies in which skin conductance was used as an indicator of anxiety [38,39]. Yet this contradiction might be specific to the group targeted by the intervention.…”
Section: Interventions For Adultscontrasting
confidence: 72%
“…While the users watched the films, skin conductance was measured and recorded using electrodes on the index and middle finger of the left hand of the participant. The study reported that skin conductance response was not related to changes in anxiety levels, which is contradictory to the findings of other studies in which skin conductance was used as an indicator of anxiety [38,39]. Yet this contradiction might be specific to the group targeted by the intervention.…”
Section: Interventions For Adultscontrasting
confidence: 72%
“…A recent study by Ihmig et al, showed ML models can be used to detect anxiety in subjects with spider fear using ECG and respiratory signals [23]. In the current study, we tested how well the ML models can predict the ADys in anxiety disorder from ECG and respiratory signals recorded during a sleep study.…”
Section: Discussionmentioning
confidence: 94%
“…Among the emerging technologies that can contribute to the treatment of anxiety, depression and stress disorders, VR appears to be the most exciting and advanced [ 14 , 34 ]. Increasingly more studies confirm the efficacy of VR therapies in fields such as psychology and psychiatry [ 9 , 35 , 36 ]. Our results also confirm the efficacy of the applied VR-based therapy in reducing the symptoms of stress.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Jerdan et al concluded that VR is a promising form of relaxation [ 13 ]. However, most studies on the use of VR are related to the treatment of anxiety disorders, including arachnophobia [ 36 , 37 , 38 , 39 ] or social phobia, where Gebara et al described improvement in the area of a social anxiety disorder (SAD) across all scales used, and their study showed that exposure to VR leads to better treatment adherence and a reduction in SAD symptoms [ 40 ]. In their study, Urech et al observed an improvement in SAD symptoms as compared to pre-study and follow-up assessment and suggested that VR is a feasible and promising therapy medium [ 35 ].…”
Section: Discussionmentioning
confidence: 99%